Computation and Early Chinese Thought. - Johnson, CarlM. (Asian Philosophy, 2012)
In recent years, it has become conventional to think of the world using metaphors taken from computation. Some have even suggested that the world itself is a kind of cosmological computer. In order to compare these suggestions to the process interpretation of early Daoism, I define computation as ‘a process in which the fact that one system is rule governed is used to make reliable correlations to another rule governed system’ and apply this definition to Yijing divination. I find that early Chinese thinking about the dao is similar to computation in certain respects, but adds elements of appropriateness, novelty, and scope that are lacking in contemporary thought.